Interações intermoleculares e topologia molecular no empacotamento cristalino de 3-amino-4-halo-5-metilisoxazóis - Meyer, Alexandre Robison (2013)
In this work is described the intermolecular interactions and the molecular topology present in the crystal packing of 3-amine-4-halo-5-methylisoxazoles. First was described the obtention of the 3-amine-4-halo-5-methylisoxazoles by halogenations of the compound 3-amine-5-methylisoxazol with N-chlorosuccinimide, N-bromosuccinimide and N-iodoosuccinimide. The crystal packing of the 3-amine-4- halo-5-methylisoxazoles show a great variety of intermolecular interactions such as: hydrogen bonding, halogen bonding, π π interactions and C-H π interactions. Further analysis of crystal packing showed that these compounds have a molecular coordination number equal to 14. The correlation between molecule molecule energy contact and the contact area between the molecules showed that, with the exception of dimmers formed by strong hydrogen bonds, all the other interactions have a large dependence of the contact area. The melting enthalpy of the 3-amine-4- halo-5-methylisoxazoles grows with the increases of the total energy of the contacts of the clusters, showing that these physic property depends of the intermolecular interactions present in the crystal. The analysis of theory levels used to determine the molecule molecule energies contact demonstrates that, when is used the method counterpoise for basis set superposition error (BSSE), the level of theory MP2/Augcc- pVDZ show energy values very close to the energy at the MP2/cc-pVTZ level of theory. The functional B97-D and ωB97X-D, based on the DFT theory, also showed satisfactory energy values, very close to those obtained by MP2.